163 Submaximal Angioplasty for Symptomatic Intracranial Atherosclerosis A Prospective, Phase I Study. (August 2015) - Dumont, Travis Michael; Sonig, Ashish; Mokin, Maxim; Eller, Jorge Luis; Sorkin, Grant C.; Snyder, Kenneth V.; Hopkins, L. Nelson; Levy, Elad I.; Siddiqui, Adnan Hussain
Abstract : INTRODUCTION: Intracranial-atherosclerotic disease (ICAD) accounts for approximately 10% of ischemic-strokes. The recent SAMMPRIS study displayed a high incidence of perioperative complications (15%) for treatment of ICAD with stenting. Although the incidence of stroke was lower in the medical arm, recurrent stroke was found in 12% of patients despite aggressive medical management, suggesting that intervention may remain a viable option for ICAD if perioperative risk is minimized. Angioplasty without stenting represents an alternative and understudied revascularization treatment for ICAD. Submaximal angioplasty limits the thromboembolism risk, vessel perforation, and reperfusion hemorrhage. We conducted a prospective phase I trial designed to assess the safety of submaximal angioplasty in patients with symptomatic ICAD. METHODS: This study was approved by the local institutional review board. Demographic and clinical data were prospectively collected. Angioplasty was performed for patients with symptomatic ICAD (significant-stenosis =70%) with a balloon undersized to approximately 50% to 70% of the nondiseased vessel diameter. The primary outcome measure was the incidence of periprocedural complications (combined rate of death, stroke, and hemorrhage occurring within 30 days and at 1 year). RESULTS: Among 65 patients screened with symptomatic ICAD, 24 had significant angiographic stenosis that met the inclusion criteria of this study. Mean age was 64.08 years (median 65 years; standard deviation + 11.24), most were men (62.5%), and most were white (66.67%). Many patients had vascular disease concomitants, including hypertension (95.8%), hyperlipidemia (70.83%), smoking history (54.1%), and diabetes mellitus (45.8%). Coronary artery disease (37.33%) and previous stroke or TIA (45.83%) were present frequently. Most patients (75%) had anterior circulation stenosis. The mean preprocedure stenosis was 80.16% (median 80%, range 70%-95%). Successful angioplasty was performed in all patients, with a mean postangioplasty stenosis of 54.62% (median 55.5%, range 31%-78%). Rates of ischemic stroke in the territory of the treated artery were 0% within 30 days and 5.55% (in the only patient who presented with restenosis) at 1 year. The mortality and hemorrhage rate was 0%. CONCLUSION: Submaximal angioplasty for symptomatic ICAD is a safe and effective technique. None of the patients had ischemic stroke in the first 30 days, and only 1 patient presented with symptomatic restenosis leading to ischemic stroke during 1 year of follow-up.